Ultrasonic investigation of the pressure profile on the faying surface of fastened aluminum plates. (March 2021) - Jerome, Trevor W.; Shepherd, Micah R.; Hambric, Stephen A.
Graphical abstract: Highlights: Ultrasonic probing of a contact interface is explored with and without preload. Multiple assemblies of the structure provide a robust dataset. A washer-type load cell indicates the normal force at the interface. Interfacial pressure is accurately inferred from the measurements. Finite element simulation supports the accuracy of the method. Abstract: Machines, buildings, and vehicles often use fasteners to connect structural elements. Screws and bolts introduce a pressure profile on joint interfaces that varies under different material parameters, preloads, and assembly conditions. Characterization of interfacial pressure at the faying surface of a joint is helpful for understanding the dynamics of the entire built-up system. Examples of interfacial measurements in the literature utilize ultrasonic methods. Some of these previous studies have used separate calibration specimens to convert qualitative ultrasonic measurements to quantitative pressure at an interface. An experiment presented here measured the quantitative distribution of pressure between fastened aluminum plates using an ultrasonic probe and force-sensing washer, without the need of a calibration specimen and test. Beyond traditional measurement methods of this type, boundary effects near the fastener were also accounted for. Scans using this method match finite element results, lending to the utility of the new procedure. The new method has shown to be accurate and more advantageous when compared to previous methods.